2013
DOI: 10.1177/1934578x1300801131
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents of Trifolium pratense spp. nivale Quantified at Different Growth Stages, and Evaluation of their Antimicrobial Activity

Abstract: The composition of the volatile fraction of Trifolium pratense L. ssp. nivale (Sieber) Asch. et Gr. from the southwestern Alps was investigated. Fresh aerial parts were collected in the summer at three different growth stages, namely vegetative, flowering and fruiting. The oils obtained by steam-distillation accounted for 0.006 to 0.011% of the fresh plant material and their composition was determined by GC/FID and GC/MS. Several classes of compounds were found, with a predominance of alcohols in all phases, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Most of these compounds were proven, by many publications, to have biological activities, e.g., antimicrobial, anti-inflammatory and antioxidant [ 64 , 65 , 66 ]. Moreover, many of the major compounds and chemical groups, detected in P. ostreatus aqueous extract by GC-MS, have been reported to have antioxidant and anti-inflammatory properties; these include (S)-(+)-isoleucinol [ 67 ], N-hydroxy-N-methyl-methanamine [ 66 ], phenylethanal [ 68 , 69 ] and 2-pyrrolidinone [ 70 , 71 ]. On the other hand, GC-MS of A. bisporus extract revealed the presence of multiple antioxidant and anti-inflammatory abundant constituents and chemical groups including N-methoxy-methanamine, [ 66 ], 2-pyrrolidinone [ 70 , 71 ] and fumaric acid, 2-heptyl octyl ester [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these compounds were proven, by many publications, to have biological activities, e.g., antimicrobial, anti-inflammatory and antioxidant [ 64 , 65 , 66 ]. Moreover, many of the major compounds and chemical groups, detected in P. ostreatus aqueous extract by GC-MS, have been reported to have antioxidant and anti-inflammatory properties; these include (S)-(+)-isoleucinol [ 67 ], N-hydroxy-N-methyl-methanamine [ 66 ], phenylethanal [ 68 , 69 ] and 2-pyrrolidinone [ 70 , 71 ]. On the other hand, GC-MS of A. bisporus extract revealed the presence of multiple antioxidant and anti-inflammatory abundant constituents and chemical groups including N-methoxy-methanamine, [ 66 ], 2-pyrrolidinone [ 70 , 71 ] and fumaric acid, 2-heptyl octyl ester [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predominant constituents were alcohols (in oils of all phases of plant growth), followed by aldehydes, hydrocarbons, terpenes, phenolics, ketones, acids and esters. The chemical profiles of oils derived from different phases varied significantly – in oils from plants during the vegetative and flowering phases, the most abundant compounds were oct‐1‐en‐3‐ol and phenylacetaldehyde, while in oil extracted from plants in the fruiting phase, phenylacetaldehyde and 2‐phenylethanol were two main components . Studies on the content of flavonols and isoflavones in flowers and leaves of T. repens demonstrated a higher concentration of polyphenols in flowers (attaining 28.70–38.80 mg of phenolics, calculated as gallic acid equivalent/g).…”
Section: Phytochemical Profile Of Trifolium Species – the Latest Findmentioning
confidence: 99%
“…The chemical profiles of oils derived from different phases varied significantlyin oils from plants during the vegetative and flowering phases, the most abundant compounds were oct-1-en-3-ol and phenylacetaldehyde, while in oil extracted from plants in the fruiting phase, phenylacetaldehyde and 2-phenylethanol were two main components. [59] Studies on the content of flavonols and isoflavones in flowers and leaves of T. repens demonstrated a higher concentration of polyphenols in flowers (attaining 28.70-38.80 mg of Table 3 The latest findings in analysis of phytochemical profile of different clover species…”
Section: Whole Plantmentioning
confidence: 99%
“…However, the use of these microorganisms presents challenges, since dosing, timing, duration and the microbiological safety of hive products require optimization for the application of these treatments. Tea tree oil nanoparticles (Santos et al, 2014), Malva sylvestris oil (Cecotti et al, 2016), aqueous and ethanolic extracts of Cinnamomum spp. and Persian salvadora (Hashish et al, 2016), macelignan and corosolic acid (Kim et al, 2018), terpenes of Thymus vulgaris (Wiese et al, 2018), among others, have been shown to have significant antibacterial effects against M. plutonius.…”
Section: Efb Controlmentioning
confidence: 99%